Polymerization of ethylene over zeolite-supported catalysts - Meshkova, I. N.; Ushakova, T. M.; Gul’tseva, N. M.; Ladygina, T. A.; Kovaleva, N. Y.; Novokshonova, L. A. (Polimery, 2022)
Zeolites including Na-form ZSM-5 (Si/Al = 42) and natural zeolite (Shivyrtuisk deposit: clinoptilolite 60 š 6%, water 14.2%) were studied as supports for olefin polymerization organometallic catalysts. Zeolite-fixed aluminoxanes, viz., anchored to the surface of the support, were prepared by partially hydrolyzing alkylaluminums (AlMe3, AlEt,Cl) with zeolite’s internal water. Thus modified, the zeolites were made to react with transition metal compounds like Cp2ZrCl2 or VOC13. The product of the reaction of zeolites’ internae water with AlMe3 was made to react with Cp2ZrCl2, and the resulting product was found to be active in the polymerization of ethylene with no additional activation carried out with MAO. In this way, an active metallocene catalyst was prepared without the use of MAO. Yet, when added as cocatalyst, MAO still activated the system, unlike the other conventional organoaluminum cocatalysts. The PE produced over the ZSM-5 (H2O)/AlMe3/Cp2ZrCl2 system had a higher M and a higher melting point than PE prepared over a homogeneous Cp2ZrCl2 + MAO catalyst system.